The Effect of Manual Therapy on Psychological Factors and Quality of Life in Lumbar Disc Herniation Patients: A Single Blinded Randomized Clinical Trial - Taşkaya, Burhan; Taşkent, İsmail; Çakıllı, Mahmut; Yılmaz, Öznur (Research Square Platform LLC, 2023)
Abstract Background The efficacy of manual therapy on psychological factors and quality of life in lumbar disc herniation patients has not been well studied. Aim This study aimed to investigate the effect of manual therapy on pain, kinesiophobia, pain catastrophizing, anxiety, depression and quality of life in patients with lumbar disc herniation (LDH). Method The study included 32 LDH patients. Patients were divided into Manual therapy group (MTG- age 39.81 ± 9.45 years) and Exercise group (EG- age 38.31 ± 9.21 years) by sealed envelope randomization. Patients were evaluated pre-study, post-study and 3-month period using the McGill-Melzack Pain Questionnaire (MMPQ), Hospital Anxiety and Depression Scale (HADS), Tampa Kinesiophobia Scale (TKS), Pain Catastrophizing Scale (PKS) and Notthingam Health Profile (NSP). The exercise group received a total of 10 sessions of stabilization exercises in 5 weeks, 2 sessions per week. In addition to stabilization exercises, mobilization applications including Anterior-Posterior Lumbar Spinal Mobilization, Lumbar Spinal Rotational Mobilization and Joint Mobilization in Lumbar Flexion Position were applied to the manual therapy group. Results It was found that HADS and TKS values decreased in the MTG group compared to the pre-treatment period (p < 0.05), while there was no difference between these values in the EG group (p > 0.05). There was a statistically significant difference in MMPQ, PCS and NHP values after treatment in both MTG and EG groups (p < 0.05). Conclusion It was found that manual therapy had positive effects on psychological factors such as pain, kinesiophobia, pain catastrophizing, anxiety, depression and quality of life in patients with LDH. ClinicalTrials.gov Identifier: NCT05804357
Keywords: Adult; Male; anxiety and depression; Lumbar Vertebrae; Depression; kinesiophobia; Middle Aged; Anxiety; Musculoskeletal Manipulations; Article; lumbar disc herniation; manual therapy; quality of life; Quality of Life; Humans; pain; Female; Single-Blind Method; Intervertebral Disc Displacement; 3. Good health